Antiproliferative and Antibacterial Potentials of Endophytic Fungi Associated with Bangladeshi Medicinal Plant Tinospora Cordifolia - Murshid, Gazi Monjur; Sohrab, Md Hossain; Ahmed, Khondoker Shahin; Masud, Mohammad Mehedi; Mazid, Md Abdul (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Endophytes provide mutual benefits and produce various biologically active secondary metabolites in plants. Our study was designed to isolate and identify fungal endophytes from fresh leaf and bark of Tinospora cordifolia, coupled with their bioactivity and preliminary chemical screening. Six endophytic fungi were isolated using surface sterilization technique. The fungi were identified by microscopic and molecular characterization and confirmed TCLE-1 as Fusarium perseae, TCLE-2 as Fusarium keratoplasticum, TCLE-3 as fusarium macrosporum, TCBE-1 as Fusarium falciforme and TCBE-2 as well as TCBE-3 leaving unidentified. Isolated strains were cultured in large scale on potato dextrose agar (PDA) medium and were extracted using ethyl acetate. Antibacterial activity of fungal extracts was performed by disc diffusion method and cytotoxicity using HeLa cell line by MTT assay. In antimicrobial test, all the fungal extracts except TCBE-2 showed moderate to potent activity in comparison to the standard kanamycin. All, except TCBE-2, demonstrated significant cytotoxic activity on HeLa cell. Preliminary chemical profiling using thin liquid chromatography (TLC) and analytical high performance liquid chromatography techniques indicated the presence of secondary metabolites in fungal extracts. In conclusion, endophytic fungi reside in the T. cordifolia, a native medicinal plant in Bangladesh, could be a potent source of putative antibacterial and anticancer compounds. Dhaka Univ. J. Pharm. Sci. 21(2): 183-194, 2022 (December)